PENENTUAN PARAMETER FISIS GUGUS GALAKSI ABELL 1185 - Rizaldi Yani H, Muhammad
Clusters of galaxies are the largest gravitational structures in the universe. Clusters of galaxies play an important role in observational cosmology. By observing galaxy clusters, knowledge such as the evolution of large-scale structures can be obtained. In this final project, the determination of the physical parameters of the galaxy cluster Abell 1185 is carried out. The physical parameters to be determined are: the distance of the galaxy cluster, the virial radii of the galaxy cluster, the members of the galaxy cluster, and the mass of the galaxy cluster. Various methods were used to determine the physical parameters of the galaxy cluster Abell 1185. The main method is Galweight which is a method of determining members of galaxy clusters and it is done by giving the weight to each galaxy sample. Galweight is a relatively new method and it is estimated that can gives better result than previous methods. Through data processing, the results obtained that the Abell 1185 has a luminosity distance of 155.28 Mpc, has a virial radii of 1.7 Mpc, has 166 members and has a mass 5.18 × 1014M?.